Numerical modeling of the formation and structure of the Orientale impact basin. Issue 5 (20th May 2013) - Potter, Ross W. K.; Kring, David A.; Collins, Gareth S.; Kiefer, Walter S.; McGovern, Patrick J.
Abstract : [1] The Orientale impact basin is the youngest and best‐preserved lunar multi‐ring basin and has, thus, been the focus of studies investigating basin‐forming processes and final structures. A consensus about how multi‐ring basins form, however, remains elusive. Here we numerically model the Orientale basin‐forming impact with the aim of resolving some of the uncertainties associated with this basin. By using two thermal profiles estimating lunar conditions at the time of Orientale's formation and constraining the numerical models with crustal structures inferred from gravity data, we provide estimates for Orientale's impact energy (2–9  × 10 25  J), impactor size (50–80 km diameter), transient crater size (∼320–480 km), excavation depth (40–55 km), and impact melt volume (∼10 6  km 3 ). We also analyze the distribution and deformation of target material and compare our model results and Orientale observations with the Chicxulub crater to investigate similarities between these two impact structures. Key Points: Numerical models of the Orientale basin‐forming impact undertaken Orientale basin attributes, including impact energy and melt volume, estimated Model results and Orientale observations are compared with the Chicxulub crater